(untitled) (Canadian Medical Education Journal, 2016)
Background: A current challenge in medical education is the steep exposure to the complexity and uncertainty of clinical practice in early clerkship. The gap between pre-clinical courses and the reality of clinical decision-making can be overwhelming for undergraduate students. The Learning-by-Concordance (LbC) approach aims to bridge this gap by embedding complexity and uncertainty by relying on real-life situations and exposure to expert reasoning processes to support learning. LbC provides three forms of support: 1) expert responses that students compare with their own, 2) expert explanations and 3) recognized scholars’ key-messages. Method: Three different LbC inspired learning tools were used by 900 undergraduate medical students in three courses: Concordance-of-Reasoning in a 1st-year hematology course; Concordance-of-Perception in a 2nd-year pulmonary physio-pathology course, and; Concordance-of-Professional-Judgment with 3rd-year clerkship students. Thematic analysis was conducted on freely volunteered qualitative comments provided by 404 students. Results: Absence of a right answer was challenging for 1st year concordance-of-reasoning group; the 2nd year visual concordance group found radiology images initially difficult and unnerving and the 3rd year concordance-of-judgment group recognized the importance of divergent expert opinion. Conclusions: Expert panel answers and explanations constitute an example of “cognitive apprenticeship” that could contribute to the development of appropriate professional reasoning processes.